2023
DOI: 10.1101/2023.02.27.23286311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Evaluation of Machine Learning-based Biomarkers for Major Depressive Disorder across Modalities

Abstract: Background: Biological psychiatry aims to understand mental disorders in terms of altered neurobiological pathways. However, for one of the most prevalent and disabling mental disorders, Major Depressive Disorder (MDD), patients only marginally differ from healthy individuals on the group-level. Whether Precision Psychiatry can solve this discrepancy and provide specific, reliable biomarkers remains unclear as current Machine Learning (ML) studies suffer from shortcomings pertaining to methods and data, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…The results show that for all representation-dataset configurations, no harmonization method outperformed the baseline more than one accuracy point. Note that our results are generally on-par with the current reported state-of-the art performances for both datasets [37,31,38,25,39,40,41,42].…”
Section: Domain Adaptationsupporting
confidence: 80%
“…The results show that for all representation-dataset configurations, no harmonization method outperformed the baseline more than one accuracy point. Note that our results are generally on-par with the current reported state-of-the art performances for both datasets [37,31,38,25,39,40,41,42].…”
Section: Domain Adaptationsupporting
confidence: 80%
“…This potentially indicates differential modes of association with MP. A possible explanation for these findings is the lack of a common link between brain structure and sleep quality/depressive symptoms, as highlighted previously (Olfati et al, 2024;Weihs et al, 2023;Winter et al, 2024).…”
Section: From Simple To Complex Associations Of Motor Performancementioning
confidence: 85%
“…Large-scale studies identified a link between longer sleep duration and higher GMV in basal ganglia but have failed to establish significant associations between other sleep health dimensions and GMV, such as insomnia (Schiel et al, 2023;Weihs et al, 2023). Similarly, investigations on depressive symptoms revealed either minimal effects or no significant associations between depressive symptoms/clinical depression and brain structure (for the ENIGMA-Major Depressive Disorder Working Group et al, 2016Olfati et al, 2024;Winter et al, 2022Winter et al, , 2024. Taken together, the neurobiological correlates of the interplay between sleep quality and depressive symptoms with MP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, prediction models should incorporate (1) personalized data from each individual, (2) sources of data clinicians use, and (3) valid measures at the individual level. In future research, it will also be important to focus on the other side of the equation as well because models in psychiatry are often specified to predict binary outcomes for disorders (eg, depressed vs control) that are known to have questionable validity and reliability . Although continued empirical and conceptual work in this area will be necessary, we believe that the field must prioritize providing ML models with substantially more data for each individual while also remaining mindful of the challenges that come with increased dimensionality.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inadequate performance of ML models in psychiatric contexts to date, it is important to consider whether ML models have sufficient information to generate accurate predictions. Herein, we discuss the importance of ample information for model performance and contrast prediction in psychiatry with successes in other fields.…”
mentioning
confidence: 99%